A study on optimization of anode groundbeds for cathodic protection of deep well casings based on the boundary element method. Issue 8 (8th March 2022) - Zhao, Qian; Du, Yanxia; Zhuang, Dawei; Li, Qiongwei; Wang, Xiaoyong
Abstract: As a kind of basic facility in oil and gas exploitation, the deep well casing is often subjected to corrosion. Cathodic protection (CP) is an important technology to mitigate the corrosion of the deep well casing. However, the casing works in a deep well thousands of meters deep underground and passes through different stratigraphic structures with various soil environments. Besides this,   in a casing well group including multiple casings, there are interactions between different casings. These problems make it difficult to design the anode groundbeds for the CP of the deep well casings and evaluate the effectiveness of CP system. Therefore, the optimization of anode groundbeds for CP of deep well casings was studied based on the boundary element method in this paper. The polarization behaviors of steel casing in different depths were measured in the field. And then the mathematical model for the CP of the deep well casing was built based on the geometric structure of casing, stratified soil resistivity, and polarization characteristics. The optimum design parameters of anode groundbeds for casing CP were explored by a numerical simulation with the boundary element method to provide a reference for the design and evaluation of CP systems for deep well casings. Abstract : A mathematical model for the cathodic protection (CP) of the deep well casing was built based on the geometric structure of casing, stratified soil resistivity, and polarization characteristics. The optimum design parameters of anode groundbeds for casing cathodic protection were explored by a numerical simulation with the boundary element method to provide a reference for the design and evaluation of CP systems for deep well casings.